2023
DOI: 10.1126/science.add7328
|View full text |Cite
|
Sign up to set email alerts
|

RAD51 bypasses the CMG helicase to promote replication fork reversal

Abstract: Replication fork reversal safeguards genome integrity as a replication stress response. DNA translocases and the RAD51 recombinase catalyze reversal. However, it remains unknown why RAD51 is required and what happens to the replication machinery during reversal. We find that RAD51 uses its strand exchange activity to circumvent the replicative helicase, which remains bound to the stalled fork. RAD51 is not required for fork reversal if the helicase is unloaded. Thus, we propose that RAD51 creates a parental DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…In contrast, fork resection was only detected after Aphidicolin treatment in RNH2B‐depleted cells (Fig 7A), which supports the view that RNase H2 is dispensable for the resection of nascent DNA when the replisome is fully blocked. To confirm that this differential effect of HU and Aphidicolin on fork resection was specific to RNH2B‐deficient cells, we next monitored fork resection in the absence of SMARCAL1, a DNA translocase promoting fork reversal (Quinet et al , 2017; Liu et al , 2023) and required for the resection of nascent DNA independently of RNA:DNA hybrids. We found that SMARCAL1‐depleted cells were equally defective for fork resection in the presence of HU or aphidicolin (Fig EV5B) and that the effect of RNaseH2 and SMARCAL1 depletion on resection is epistatic (Fig EV5C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, fork resection was only detected after Aphidicolin treatment in RNH2B‐depleted cells (Fig 7A), which supports the view that RNase H2 is dispensable for the resection of nascent DNA when the replisome is fully blocked. To confirm that this differential effect of HU and Aphidicolin on fork resection was specific to RNH2B‐deficient cells, we next monitored fork resection in the absence of SMARCAL1, a DNA translocase promoting fork reversal (Quinet et al , 2017; Liu et al , 2023) and required for the resection of nascent DNA independently of RNA:DNA hybrids. We found that SMARCAL1‐depleted cells were equally defective for fork resection in the presence of HU or aphidicolin (Fig EV5B) and that the effect of RNaseH2 and SMARCAL1 depletion on resection is epistatic (Fig EV5C).…”
Section: Resultsmentioning
confidence: 99%
“…It is now well established that stressed forks are extensively remodeled through a process involving fork reversal, in which nascent DNA strands reanneal to form a four‐way structure resembling a Holliday junction (Neelsen & Lopes, 2015). Fork reversal is mediated by the RAD51 recombinase and by different DNA translocases, including SMARCAL1, HLTF and ZRANB3 (Quinet et al , 2017; Liu et al , 2023). Since the regressed arm resembles a one‐ended DSB, it is susceptible to nucleolytic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…In response to replication stress, replication forks reverse into four-way junctions through annealing of the nascent DNA strands (2,9). Reversed forks must be protected from nucleolytic attack to prevent fork attrition (10,13,15,48,49).…”
Section: Resultsmentioning
confidence: 99%
“…The fork reversal activities of SMARCAL1, ZRANB3, and HTLF lead to the degradation of nascent strand DNA in BRCA1/2-deficient cells upon treatment with HU (9,10). Given our results that suggest that RAD54L may function similarly to these established fork remodelers, we tested if RAD54L loss prevents nascent strand DNA degradation in BRCA1/2-deficient cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation